Compensation of time-delay for control of civil engineering structures. - Agrawal, A.K (Earthquake engineering & structural dynamics.)
Time-delay is an important issue in structural control. Applications of unsynchronized control forces due to time-delay may result in a degradation of the control performance and it may even render the controlled structures to be unstable. In this paper, a state of the art review for available methods of time delay compensation is presented. Then, five methods for the compensation of fixed time delay are presented and investigated for active control of civil engineering structures. These include the recursive response method, state-augmented compensation method, controllability based stabilization method, the Smith predictor method and the Pade approximation method, all are applicable to any control algorithm to be used for controlled design. Numerical simulations have been conducted for MDOF building models equipped with an active control system to demonstrate the stability and control performance of these time delay compensation methods. Finally, the stability and performance of the phase shift method, that is well known in civil engineering applications, have also been critically evaluated through numerical simulations.